Student-centered approach and alternative assessments to improve students' learning domains during health education sessions - Zulkifli Ahmad Fahim (Sciendo, 2019)
Study aim: The purpose of this study was to evaluate the effects of astudent-centered approach and alternative assessments on students' learning domains (i.e., cognitive, affective, psychomotor) during health education learning sessions.